2013
DOI: 10.1038/nbt.2509
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of metabolic pathways in yeast mitochondria improves the production of branched-chain alcohols

Abstract: Efforts to improve the production of a compound of interest in Saccharomyces cerevisiae have mainly involved engineering or overexpression of cytoplasmic enzymes. We show that targeted expression of metabolic pathways to mitochondria can increase production levels compared with expression of the same pathways in the cytoplasm. Compartmentalisation of the Ehrlich pathway into mitochondria increased isobutanol production by 260%, whereas overexpression of the same pathway in the cytoplasm only improved yields by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
364
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(375 citation statements)
references
References 44 publications
4
364
0
2
Order By: Relevance
“…The findings about the ER subcellular localization of MmFar1p (mouse fatty acid reductase) is relevant to engineering pathway compartmentalization as a way to optimize bioproduction or tailor product distribution (Avalos et al, 2013;Sheng et al, 2016;. Our observation that overexpression of a fatty acid desaturase led to improvements in fatty acid products in S. cerevisiae as in Y. lipolytica (Qiao et al, 2015) points to commonalities in fatty pathway engineering in both organisms.…”
Section: Discussionmentioning
confidence: 81%
“…The findings about the ER subcellular localization of MmFar1p (mouse fatty acid reductase) is relevant to engineering pathway compartmentalization as a way to optimize bioproduction or tailor product distribution (Avalos et al, 2013;Sheng et al, 2016;. Our observation that overexpression of a fatty acid desaturase led to improvements in fatty acid products in S. cerevisiae as in Y. lipolytica (Qiao et al, 2015) points to commonalities in fatty pathway engineering in both organisms.…”
Section: Discussionmentioning
confidence: 81%
“…While broad substrate specificity of PsTNMT had been previously described 34 , we present the first experimental evidence of its acceptance of scoulerine and cheilanthifoline as substrates. Possible solutions for overcoming the problem of PsTNMT promiscuity in our system would include screening for orthologous plant enzymes with narrower substrate specificity, enzyme engineering 42 , substrate channelling and/or spatio-temporal sequestration of the reactions 43,44 .…”
Section: Rs)-norlaudanosoline (Nor) (S)-reticuline (Ret) (S)-scoulmentioning
confidence: 99%
“…Substantial advances showed that localizing the entire Ehrlich pathway to either mitochondria or cytosol could obtain equally improved titers of approximately 630 mg L À1 of isobutanol. [24,25] However, localization to mitochondria results in much greater yields relative to its cytosolic counterpart (14.2 vs. 6.4 mg g À1 glucose). More improved titers were reported for isobutanol production in S. cerevisiae (1.6 g L À1 ) by a combination of multiple strategies including overexpression of the fully localized cytosolic ilv2, ilv5, and ilv3 genes, introduction of a transhydrogenase-like shunt to regenerate NADPH, and deletion of the pdc gene.…”
Section: G L à1mentioning
confidence: 99%